ChemInform Abstract: Copper N‐Heterocyclic Carbene: A Catalyst for Aerobic Oxidation or Reduction Reactions. Issue 18 (April 2016) - Zhan, Le‐Wu; Han, Lei; Xing, Ping; Jiang, Biao
Abstract: Copper N‐heterocyclic carbene complexes are suitable catalysts for both the aerobic oxidation and the reduction reactions.